Preparation and modification of zeolite A from kaolin for catalytic methanation of carbon dioxide. Issue 2 (25th January 2023) - Son, Do Cao; Anh, Vo Thi Kieu; Thom, Nguyen Thi; Nguyen, Huynh Le Thanh; Hai, Le Viet; Thien, Co Thanh; Hoang, Nguyen Thai; Lam, Tran Dai; Nam, Pham Thi; Trang, Nguyen Thi Thu
Abstract: Different types of zeolite including Zeolite A are prepared from natural kaolin originated in Vietnam. Raw kaolin was collected from Phu Tho, Vietnam, underwent metakaolization at 650 °C within 2 hours and alkalination with NaOH to synthesize various zeolitic samples. Various characterization techniques were performed, including X‐ Ray Diffraction, Fourier‐transform infrared spectroscopy, and Scanning Electron Microscopy. Different concentrations of NaOH were utilized to study the difference of the prepared zeolite. Nickel‐doped zeolite A samples with different nickel loading were also prepared via ion exchange method and were employed as catalyst for the hydrogenation of carbon dioxide (CO2 ) to obtain methane (CH4 ). The best catalytic activity of 55.2 %CO2 conversion and 92.7 %CH4 selectivity was achieved with 10 %Ni/ZM1 at 350 °C, 1 atm, H2 :CO2 ratio of 4:1, and gas hourly space velocity of 9, 000 mL.g ‐1 .h ‐1 . This study demonstrates a promising pathway of modifying Vietnamese natural kaolin as a low‐cost but an effective alternative material for the preparation of zeolite A and its application in the carbon dioxide methanation reaction. Abstract :